Perencanaan Reservoir Perusahaan Daerah Air Minum Ibu Kota Kecamatan Angsana: (Studi Kasus Kecamatan Angsana, Kabupaten Tanah Bumbu, Provinsi Kalimantan Selatan) - Sofyan, Chemis; Pratiwi, Yunita Eka; Ndibale, Wa (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2025)
Clean water is a fundamental necessity for community life, directly impacting health, economy, and social welfare. The availability of continuous and quality clean water is a major challenge for regions experiencing rapid population growth, such as Angsana District. Sustainable clean water supply in Angsana District is constrained by the insufficient capacity of the existing reservoir (300 m³) to meet the continuously increasing demand due to population growth. This study aims to: (1) project clean water demand for the next 20 years (2024–2043); (2) determine the required reservoir capacity; and (3) design an appropriate additional reservoir. Using a quantitative approach, population projection was conducted using the geometric method, while water demand was calculated based on domestic and non-domestic needs in accordance with Indonesian National Standards SNI 7509:2011 on Technical Planning Procedures for Drinking Water Supply Systems and SNI 6774:2023 on Planning Procedures for Package Unit Water Treatment Plants. The results show a population growth rate of 2.26% per year, with a projected population of 36,672 people by 2043. Peak hour water demand is 105.7 liters/second, and maximum daily demand (Qhm) is 5,333.3 m³/day. According to SNI 6774:2023, the required effective reservoir capacity is 15% of Qhm, which is 800 m³. Considering the existing 300 m³ reservoir, an additional reservoir with a capacity of 500 m³ is needed. The proposed technical design for the ground storage reservoir is rectangular with dimensions of 15 m (length) × 10 m (width) × 3.33 m (total height), an effective water height of 2.83 m, and includes freeboard and dead storage.